Sequencing BPS spectra - Gukov, Sergei; Nawata, Satoshi; Saberi, Ingmar; Stos̆ić, Marko; Sułkowski, Piotr (Journal of high energy physics, 2016)
This paper provides both a detailed study of color-dependence of link homologies, as realized in physics as certain spaces of BPS states, and a broad study of the behavior of BPS states in general. We consider how the spectrum of BPS states varies as continuous parameters of a theory are perturbed.
Gesehen am 06.04.2018